Relacionamento interpessoal e mídia: as relações de amizade entre as personagens do programa castelo Rá-Tim-Bum - Moura, Luciana Teles (2007)
This work investigated the friendship relations between children of a childish fiction program, propagated by an educational broadcasting station. The investigated program - Castelo Rá-tim-bum - is recognized by the public and by the criticism as one of the most successful cultural products developed by Brazilian television. Through a documentary research were analyzed 20 of 90 episodes those component the series, and the choice was random. The relationships between the central characters of the children's program were analyzed from 11 psychosocial dimensions: friendship network, similarity, communication, cooperation, support, companionship, intimacy, affective aspects, conflict, aggressiveness and competition. The proceeded data were compared with data from investigations of researchers those dedicate themselves to the study of friendship involving children of the real world in order to measure nearness and distancing between reality and fiction. Generally, was realized that the friendships portrayed in the program are very similar to real friendships, existing, however, some level of idealization of this relationships.